2017
DOI: 10.1186/s13014-017-0778-z
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of inter- and intra fractional partial bladder wall movement using implanted fiducial markers

Abstract: BackgroundCurrent adaptive and dose escalating radiotherapy for muscle invasive bladder cancer requires knowledge of both inter-fractional and intra-fractional motion of the bladder wall involved. The purpose of this study is to characterize inter- and intra-fractional movement of the partial bladder wall using implanted fiducial markers and a real-time tumor-tracking radiotherapy system.MethodsTwo hundred fifty one sessions with 29 patients were analysed. After maximal transurethral bladder tumor resection an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 35 publications
0
5
0
1
Order By: Relevance
“…As the bladder tumour is relatively rigid and non-elastic compared with non-tumourbearing bladder regions, it may be minimal [32,107]. One conclusion that can be drawn from this work is that despite these limitations when GTV is present on the superior and anterior regions of the bladder, larger positional variation should be expected than when GTV is present at other regions of the bladder [34,36,41,106,107].…”
Section: Determining Magnitude Of Target Motionmentioning
confidence: 82%
See 1 more Smart Citation
“…As the bladder tumour is relatively rigid and non-elastic compared with non-tumourbearing bladder regions, it may be minimal [32,107]. One conclusion that can be drawn from this work is that despite these limitations when GTV is present on the superior and anterior regions of the bladder, larger positional variation should be expected than when GTV is present at other regions of the bladder [34,36,41,106,107].…”
Section: Determining Magnitude Of Target Motionmentioning
confidence: 82%
“…Consensus drawn from studies assessing inter-fraction change is that bladder motion occurs predominantly in the cranial direction (as a result of bladder filling) and [32] Cine-MR motion up 57 mm identified over 28 min Gronborg et al, 2015 [33] Intra-fractional motion over 10 min captured by 5 mm Nishioka et al, 2017 [34] Motion predominantly superior and anterior direction; Intra-fractional motion over 10 min captured by 5 mm Dees-Ribbers et al, 2014 [13] Motion between a full bladder and an empty bladder protocol does not differ Yee et al, 2010 [35] Inter-fraction motion predominantly anterior direction 0 Fiducial marker Chai et al, 2010 [36] Sondergaard et al, 2010 [37] GTV deformation and motion assessed using lipiodol Non-ART PTV: CTV þ15 mm PoD-PTVs: Small ¼ smallest bladder (as seen on planning CT/CBCTs) þ 5 mm Medium ¼ halfway between small and large Large ¼ PTVcomp of CT and CBCTs þ5 mm Alternative method PoD-PTVs: Small ¼ PTVcomp of 2 smallest bladder (as seen on planning CT/CBCTs) þ 5 mm Medium and large as above Small PoD-PTV generated using 2 smallest volumes as seen on planning and CBCT days 1e5 was selected more frequently than initial method Online re-optimisation using PTV; Iso: bladder þ5 mm Aniso: bladder þ7 mm (S), 5 mm (A,R,L,I,P) Pop: bladder þ14 mm (A,S), 9 mm (P), 5 mm (R,L,I)…”
Section: Determining Magnitude Of Target Motionmentioning
confidence: 99%
“…Additional studies have shown an impact of time on the movement of tumors or structures near the bladder during the patient on-couch time. The maximum bladder wall movements from the start of a treatment session increased intrafractionally with time, as found in the study by Nishioka using implanted fiducial markers and stereoscopic fluoroscopy [34]. Eijkelenkamp et al analyzed the deformations of the GTV in dependence on adaptation time from repeated imaging on an MR-Linac during five dose fraction [35].…”
Section: Discussionmentioning
confidence: 92%
“…Hallan movimientos intrafracción de la pared vesical discretamente menores para los pacientes tratados con la vejiga llena, en tanto que los cambios interfracción son solo ligeramente mayores, variando R y v para estos últimos desde 1 mm en la parte caudal hasta 12 mm en la craneal-anterior. Nishioka et al, 142 evalúan los movimientos inter e intrafracción de la parte de la pared en la que está localizado el tumor mediante marcadores de oro en la pared vesical. Hallan, al igual que en Dees-Ribbers et al 141 , que los mayores movimientos fueron en las direcciones cráneo-caudal (de −13.6 mm a 10.8 mm) y antero-posterior (de −10.0 mm a 7.7 mm) para el movimiento interfracción (cuantil 95%), aunque los valores de R y v hallados son menores, alrededor de 5 mm.…”
Section: Cambios Anatómicosunclassified